The house of Hades - Riordan, Rick. (New York : Disney/Hyperion Books, 2013)
Greek and Roman demigods from the Prophecy of Seven must work together to seal the Doors of Death--and help Percy and Annabeth escape the Underworld in the process.
School Library Journal, February 2014.
Horn Book, April 2014.
Kirkus Review, November 2013.
4.7
5-8
680L
Keywords: Hera, -- (Greek deity) -- Juvenile fiction; Hera, -- (Greek deity) -- Fiction; Hera (Greek deity -- Fiction; Mythology, Roman -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Giants -- Juvenile fiction; Camps -- Juvenile fiction; Gaia (Greek deity) -- Juvenile fiction; Mythology, Roman -- Fiction; Mythology, Greek -- Fiction; Giants -- Fiction; Camps -- Fiction; Gaia (Greek deity) -- Fiction; Roman mythology -- Fiction; Greek mythology -- Fiction; Gaia (Greek deity) -- Fiction; Hera (Greek deity) -- Fiction; Fantasy; Fantasy fiction; Action and adventure fiction